Current collector, preparation method thereof and lithium battery

By using current collectors modified with pore structure and anionic surfactant in lithium batteries, the problems of irreversibility and inhomogeneity of lithium metal batteries during deposition and peeling are solved, and the uniform deposition of lithium metal and the improvement of safety performance are achieved.

CN120221667APending Publication Date: 2025-06-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510336316.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

Lithium metal batteries have irreversibility and unevenness during the deposition and peeling process, resulting in volume expansion, safety hazards and the occurrence of "dead lithium", which limits its practical application.

Method used

A current collector is employed, which comprises a substrate layer and a modification layer. The substrate layer is provided with a pore structure, containing copper and lithium-philic metals, and the modification layer contains anionic surfactant. The current collector increases the deposition area of ​​lithium ions, reduces the current density, and promotes the uniform deposition of lithium metal through anionic surfactant, thereby alleviating the irregular growth of lithium dendrites.

Benefits of technology

Effectively reduce the volume expansion caused by lithium deposition, promote the uniform deposition of lithium metal, reduce safety risks, and improve the overall performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120221667A_ABST
    Figure CN120221667A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a current collector, a preparation method thereof and a lithium battery. The current collector comprises a base material layer and a modification layer, and the base material layer is provided with a pore structure and contains copper and lithium-loving metal; the modification layer is arranged on at least one surface of the base material layer and comprises an anionic surfactant. According to the current collector, volume expansion caused by lithium deposition can be reduced, uniform deposition of lithium metal can be induced, and the safety problem caused by irregular growth of lithium dendrites is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of batteries, and particularly to a current collector, a preparation method thereof, and a lithium battery. Background Art

[0002] In the currently commercialized battery energy storage systems, although the energy density of lithium-ion batteries is significantly higher than that of other battery systems, the energy density of commercial lithium-ion batteries is still far lower than that provided by fossil fuels such as gasoline. In addition, the rapid development of portable electronic devices such as laptops and mobile phones has also posed an increasing challenge to the existing energy system. It is urgent to develop the next generation of energy storage battery systems with intrinsically high energy density and high performance.

[0003] Different from lithium-ion batteries, metallic lithium can be used independently as the anode material of the battery and paired with different types of cathode materials such as elemental sulfur and oxygen, providing the highest theoretical specific capacity (3860 mAh / g), the lowest physical density (0.59 g / cm 3 ) and the lowest electrochemical potential (-3.04 V vs. SHE). Therefore, lithium metal batteries have received unprecedented attention, and with the continuous development of rechargeable lithium metal systems, the advantages of metallic lithium anodes have been gradually exploited. However, the deposition and stripping of lithium metal batteries are highly irreversible and inhomogeneous, which also pose significant obstacles to the practical application of lithium metal batteries. Among them, the unstable solid electrolyte interphase, the resulting side reactions, low Coulombic efficiency, safety hazards caused by dendrite growth, severe volume expansion, and a large amount of "dead lithium" are common and prominent problems faced in the practical application of lithium metal batteries. Summary of the Invention

[0004] In view of this, the present invention provides a current collector, a preparation method thereof, and a lithium battery. The current collector can reduce the volume expansion caused by lithium deposition, induce uniform deposition of lithium metal, and alleviate the safety problems caused by the irregular growth of lithium dendrites.

[0005] To achieve the above-mentioned invention object, the present invention provides the following technical solutions:

[0006] In the first aspect, the present invention provides a current collector, which includes:

[0007] (a) A substrate layer, which is provided with a pore structure; the substrate layer contains copper and a lithiumophilic metal;

[0008] (b) A modification layer, which is disposed on at least one surface of the substrate layer; the modification layer includes an anionic surfactant.

[0009] In the embodiments of the present invention, the lithiumophilic metal includes at least one of indium, tin, aluminum, and silver.

[0010] Preferably, the particle size D of the lithiumophilic metal 50 is 50 to 200 nm.

[0011] Preferably, the mass ratio of copper to the lithiumophilic metal is (5 to 6):(0.05 to 0.2).

[0012] In the embodiment of the present invention, the pore structure includes a plurality of vertical channels penetrating the substrate layer.

[0013] Preferably, the pore diameter of the pore structure is 20 to 60 nm.

[0014] Preferably, the porosity of the substrate layer is 30% to 50%.

[0015] In the embodiment of the present invention, the anionic surfactant includes at least one of sodium dodecyl sulfonate, anionic polyacrylamide, and sodium ethoxylated fatty acid methyl ester sulfonate.

[0016] Preferably, the thickness of the substrate layer is 6 to 13 μm.

[0017] Preferably, the thickness of the modification layer is 1 to 3.5 μm.

[0018] In a second aspect, the present invention provides a method for preparing the above current collector, including the following steps:

[0019] S1, mixing copper oxide, polyethersulfone, a dispersant, a lithiumophilic metal, and a first solvent, and performing ball milling to obtain a first slurry;

[0020] Coating the first slurry onto a carrier film, then placing it in a second solvent for a phase inversion reaction, and after a first drying treatment, obtaining a green body;

[0021] S2, performing a carbon removal treatment on the green body to obtain a base layer; performing a reduction sintering treatment on the base layer to obtain a substrate layer;

[0022] S3, mixing the anionic surfactant and an aqueous solution of a binder dispersant to obtain a second slurry;

[0023] Coating the second slurry on the surface of the substrate layer, and after a second drying treatment, obtaining the current collector.

[0024] In step S1 of the preparation method of the present invention:

[0025] Preferably, the mass ratio of copper oxide, polyethersulfone, the dispersant, and the lithiumophilic metal is 7:(1.9 to 1.95):1:(0.05 to 0.2).

[0026] Preferably, the particle size D of copper oxide 50 is 10 to 100 nm.

[0027] In an embodiment of the present invention, the dispersant includes polyvinylpyrrolidone and / or hydroxypropyl methylcellulose.

[0028] In an embodiment of the present invention, the first solvent includes N-methylpyrrolidone.

[0029] Preferably, the viscosity of the first slurry is 5000-8000 mPa·s.

[0030] Preferably, the speed of the ball milling treatment is 500-800 rpm / min, and the time of the ball milling treatment is 3-10 h.

[0031] In an embodiment of the present invention, the second solvent includes ethanol.

[0032] Preferably, the time of the phase inversion reaction is 4-8 h.

[0033] Preferably, the temperature of the first drying treatment is 80-100 °C, and the time of the first drying treatment is 12-24 h.

[0034] In step S2 of the preparation method of the present invention:

[0035] Preferably, the temperature of the carbon removal treatment is 380-500 °C, and the time of the carbon removal treatment is 2-4 h.

[0036] Preferably, the gas atmosphere of the reduction sintering treatment is a mixed gas atmosphere of hydrogen and an inert gas, and the volume ratio of hydrogen to the inert gas is (4-6):(94-96).

[0037] Preferably, the temperature of the reduction sintering treatment is 750-950 °C, and the time of the reduction sintering treatment is 4-8 h.

[0038] In step S3 of the preparation method of the present invention:

[0039] In an embodiment of the present invention, the binder dispersant includes carboxymethyl cellulose.

[0040] Preferably, the concentration of the binder dispersant aqueous solution is 1 wt% - 2 wt%.

[0041] Preferably, the mass ratio of the anionic surfactant to the binder dispersant aqueous solution is (0.5-3):100.

[0042] Preferably, the temperature of the second drying treatment is 100-120 °C, and the time of the second drying treatment is 12-24 h.

[0043] In a third aspect, the present invention provides a lithium battery, which includes the above current collector and / or the current collector prepared by the above preparation method.

[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0045] The current collector provided by the present invention includes a substrate layer and a modification layer. The substrate layer is provided with a pore structure, which contains copper and a lithiumophilic metal; the modification layer is disposed on at least one surface of the substrate layer and includes an anionic surfactant.

[0046] Among them, the pore structure of the current collector substrate layer can increase the deposition area of lithium ions and reduce the current density. The pore structure provides buffer sites for unsupported lithium metal, thereby reducing the volume expansion caused by lithium deposition;

[0047] The lithiumophilic metal of the current collector substrate layer is compounded with copper to a certain extent, which can enhance the lithiumophilic property of the current collector, induce uniform deposition of lithium metal, and alleviate the safety problems caused by the irregular growth of lithium dendrites;

[0048] The anionic surfactant of the current collector modification layer can construct an electrostatic field, enhance the two-dimensional diffusion during the lithium ion deposition process, achieve densification deposition, promote the uniform deposition of lithium metal, and alleviate the safety hazards brought by the growth of lithium dendrites. Description of the Drawings

[0049] Figure 1 It is a preparation flow chart of a current collector with a vertical channel of lithiumophilic metal@copper composite modified by an anionic surfactant in Example 1.

[0050] Figure 2 It is a schematic structural diagram of the cross-section of the current collector in Example 1.

[0051] Figure 3 It is a scanning electron microscope image of the negative electrode surface after full charge of the battery obtained by preparing the current collector in Example 1.

[0052] Figure 4 It is a scanning electron microscope image of the negative electrode surface after full charge of the battery obtained by preparing the current collector in Comparative Example 1.

[0053] The description of the reference numerals is as follows:

[0054] 1: Substrate layer;

[0055] 2: Modification layer. Detailed Embodiments

[0056] The present invention discloses a current collector, a preparation method thereof, and a lithium battery. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make changes or appropriate modifications and combinations to the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.

[0057] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes and do not indicate or imply relative importance.

[0058] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0059] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range or individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0060] If there is no special indication, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0061] If there is no special indication, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0062] If there is no special indication, the "including" and "comprising" mentioned in the present application mean open-ended or can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or it can only include or comprise the listed components.

[0063] Specifically, the present invention adopts the following technical solutions:

[0064] In a first aspect, the present invention provides a current collector, which includes:

[0065] (a) a substrate layer provided with a pore structure; the substrate layer contains copper and a lithiumophilic metal;

[0066] (b) a modification layer disposed on at least one surface of the substrate layer; the modification layer includes an anionic surfactant.

[0067] In the present invention, the pore structure (such as a vertical channel structure, a disordered pore structure, etc.) of the current collector substrate layer can increase the deposition area of lithium ions and reduce the current density. The pore structure provides buffer sites for unsupported lithium metal, thereby reducing the volume expansion caused by lithium deposition; the lithiumophilic metal is compounded with copper to a certain extent, which can enhance the lithiumophilic property of the current collector, induce uniform deposition of lithium metal, and alleviate the safety problems caused by the irregular growth of lithium dendrites. The anionic surfactant of the current collector modification layer can construct an electrostatic field, enhance the two-dimensional diffusion during the lithium ion deposition process, achieve densification deposition, promote the uniform deposition of lithium metal, and alleviate the safety hazards brought by the growth of lithium dendrites.

[0068] In a specific embodiment of the present invention, when preparing the current collector of the present invention, a green body is first prepared by mixing copper oxide, polyethersulfone, and a lithiumophilic metal, and after carbon removal treatment and reduction sintering treatment, a substrate layer provided with a pore structure is obtained. Therefore, the copper and the lithiumophilic metal in the current collector substrate layer of the present invention are in a uniformly mixed state. The uniform compounding of the lithiumophilic metal and copper can enhance the lithiumophilic property of the current collector, induce uniform deposition of lithium metal, and alleviate the safety problems caused by the irregular growth of lithium dendrites.

[0069] In an embodiment of the present invention, the lithiumophilic metal includes at least one of indium, tin, aluminum, and silver.

[0070] Preferably, the lithiumophilic metal is indium.

[0071] As a preference, the particle size D of the lithiumophilic metal 50 is 50 - 200 nm. Exemplarily, the particle size D of the lithiumophilic metal 50 is any value among 50 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm or any value within the range formed by any two of the above values.

[0072] As a preference, the mass ratio of copper to the lithiumophilic metal is (5 - 6):(0.05 - 0.2). Exemplarily, the mass ratio of copper to the lithiumophilic metal is any value among 5:0.2, 5.2:0.15, 5.4:0.1, 5.6:0.08, 6:0.05 or any value within the range formed by any two of the above values.

[0073] In the embodiment of the present invention, the pore structure includes a plurality of vertical channels penetrating the substrate layer. The vertical channel structure can more significantly reduce the current density, avoid charge accumulation, and is beneficial to the uniformity of lithium deposition.

[0074] Preferably, the pore diameter of the pore structure is 20 - 60 nm. Exemplarily, the pore diameter of the pore structure is any value among 20 nm, 30 nm, 40 nm, 50 nm, 60 nm or any value within the range value composed of any two of the above numerical values.

[0075] Preferably, the porosity of the substrate layer is 30% - 50%. Exemplarily, the porosity of the substrate layer is any value among 30%, 35%, 40%, 45%, 50% or any value within the range value composed of any two of the above numerical values.

[0076] In the embodiment of the present invention, the anionic surfactant includes at least one of sodium dodecyl sulfonate, anionic polyacrylamide, and sodium ethoxylated fatty acid methyl ester sulfonate.

[0077] Preferably, the thickness of the substrate layer is 6 - 13 μm. Exemplarily, the thickness of the substrate layer is any value among 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or any value within the range value composed of any two of the above numerical values.

[0078] Preferably, the thickness of the modification layer is 1 - 3.5 μm. Exemplarily, the thickness of the modification layer is any value among 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or any value within the range value composed of any two of the above numerical values.

[0079] In a second aspect, the present invention provides a method for preparing the above current collector, including the following steps:

[0080] S1, Mix copper oxide, polyethersulfone (PESF), a dispersant, a lithiumophilic metal, and a first solvent, and perform ball milling treatment to obtain a first slurry;

[0081] Coat the first slurry onto a carrier film, then place it in a second solvent for phase inversion reaction, and after the first drying treatment, obtain a green body;

[0082] S2, Perform carbon removal treatment on the green body to obtain a base layer; perform reduction sintering treatment on the base layer to obtain a substrate layer;

[0083] S3, Mix the anionic surfactant and an aqueous solution of a binder dispersant to obtain a second slurry;

[0084] Coat the second slurry on the surface of the substrate layer, and after the second drying treatment, obtain the current collector.

[0085] In step S1 of the preparation method of the present invention:

[0086] As a polymer solute, polyethersulfone has the following functions: polyethersulfone can adjust the viscosity and fluidity of the slurry to ensure the uniformity and stability of the cast film; polyethersulfone can act as a binder to fix copper oxide and lithiumophilic metal; polyethersulfone is also a necessary component in the phase inversion reaction process.

[0087] Preferably, the mass ratio of copper oxide, polyethersulfone, dispersant and lithiumophilic metal is 7:(1.9 - 1.95):1:(0.05 - 0.2). Exemplarily, the mass ratio of copper oxide, polyethersulfone, dispersant and lithiumophilic metal is any value among 7:1.9:1:0.2, 7:1.92:1:0.1, 7:1.94:1:0.15, 7:1.95:1:0.05 or any value within the range value composed of any two of the above values.

[0088] Preferably, the particle size D of copper oxide 50 is 10 - 100 nm. Exemplarily, the particle size D of copper oxide 50 is any value among 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any value within the range value composed of any two of the above values.

[0089] The dispersant can improve the uniformity of the slurry and adjust the viscosity. In the embodiments of the present invention, the dispersant includes polyvinylpyrrolidone (PVP) and / or hydroxypropyl methylcellulose (HPMC).

[0090] In the embodiments of the present invention, the first solvent includes N-methylpyrrolidone (NMP).

[0091] Preferably, the viscosity of the first slurry is 5000 - 8000 mPa·s. Exemplarily, the viscosity of the first slurry is any value among 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s or any value within the range value composed of any two of the above values.

[0092] Preferably, the speed of the ball milling treatment is 500 - 800 rpm / min, and the time of the ball milling treatment is 3 - 10 h. Exemplarily, the speed of the ball milling treatment is any value among 500 rpm / min, 600 rpm / min, 700 rpm / min, 800 rpm / min or any value within the range value composed of any two of the above values, and the time of the ball milling treatment is any value among 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the range value composed of any two of the above values.

[0093] In an embodiment of the present invention, the second solvent includes ethanol. To avoid the reaction of lithiumophilic metal with water, the second solvent is a pure ethanol solvent, and water is avoided.

[0094] The phase inversion reaction process is a phase separation process of a homogeneous slurry. During the phase separation process, there is an exchange between the solvent and the non-solvent in the slurry, which transforms into a polymer-rich phase and a polymer-poor phase, thereby forming a unique microstructure, which helps to form vertical channels penetrating the substrate layer in the subsequent substrate layer. Preferably, the time of the phase inversion reaction is 4 to 8 h. Exemplarily, the time of the phase inversion reaction is any value among 4 h, 5 h, 6 h, 7 h, 8 h or any value within the range value composed of any two of the above values.

[0095] Preferably, the temperature of the first drying treatment is 80 to 100 °C, and the time of the first drying treatment is 12 to 24 h. Exemplarily, the temperature of the first drying treatment is any value among 80 °C, 85 °C, 90 °C, 95 °C, 100 °C or any value within the range value composed of any two of the above values, and the time of the first drying treatment is any value among 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or any value within the range value composed of any two of the above values.

[0096] In step S2 of the preparation method of the present invention:

[0097] During the carbon removal treatment, the high molecular solute decomposes into CO2 and water vapor under the action of high temperature. This step can remove the high molecular solute from the green body, thereby forming vertical channels penetrating the substrate layer in the substrate layer. Preferably, the temperature of the carbon removal treatment is 380 to 500 °C, and the time of the carbon removal treatment is 2 to 4 h. Exemplarily, the temperature of the carbon removal treatment is any value among 380 °C, 400 °C, 420 °C, 440 °C, 460 °C, 480 °C, 500 °C or any value within the range value composed of any two of the above values, and the time of the carbon removal treatment is any value among 2 h, 2.5 h, 3 h, 3.5 h, 4 h or any value within the range value composed of any two of the above values.

[0098] During the reduction sintering treatment, copper oxide is completely reduced to copper, and the reduction equation is as follows: CuO + H2 → Cu + H2O.

[0099] Preferably, the gas atmosphere of the reduction sintering treatment is a mixed gas atmosphere of hydrogen and inert gas, and the volume ratio of hydrogen to inert gas is (4 to 6):(94 to 96). Exemplarily, the volume ratio of hydrogen to inert gas is any value among 4:96, 5:95, 6:95 or any value within the range value composed of any two of the above values.

[0100] Preferably, the temperature of the reduction sintering treatment is 750 to 950 °C, and the time of the reduction sintering treatment is 4 to 8 h. Exemplarily, the temperature of the reduction sintering treatment is any value among 750 °C, 800 °C, 850 °C, 900 °C, 950 °C or any value within the range value composed of any two of the above values, and the time of the reduction sintering treatment is any value among 4 h, 5 h, 6 h, 7 h, 8 h or any value within the range value composed of any two of the above values.

[0101] In step S3 of the preparation method of the present invention:

[0102] In the embodiment of the present invention, the binder dispersant includes carboxymethyl cellulose (CMC).

[0103] Preferably, the concentration of the binder dispersant aqueous solution is 1 wt% to 2 wt%. Exemplarily, the concentration of the binder dispersant aqueous solution is any value among 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2 wt% or any value within the range value composed of any two of the above values.

[0104] Preferably, the mass ratio of the anionic surfactant to the binder dispersant aqueous solution is (0.5 to 3):100. Exemplarily, the mass ratio of the anionic surfactant to the binder dispersant aqueous solution is any value among 0.5:100, 1:100, 2:100, 3:100 or any value within the range value composed of any two of the above values.

[0105] Preferably, the temperature of the second drying treatment is 100 to 120 °C, and the time of the second drying treatment is 12 to 24 h. Exemplarily, the temperature of the second drying treatment is any value among 100 °C, 105 °C, 110 °C, 115 °C, 120 °C or any value within the range value composed of any two of the above values, and the time of the second drying treatment is any value among 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or any value within the range value composed of any two of the above values.

[0106] In a third aspect, the present invention provides a lithium battery, which includes the above current collector and / or the current collector prepared by the above preparation method.

[0107] In the embodiment of the present invention, the lithium battery is a lithium battery without a negative electrode.

[0108] In the embodiment of the present invention, the lithium battery further includes a positive electrode sheet and a separator.

[0109] In the embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.

[0110] In an embodiment of the present invention, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (80-99):(0.5-10):(0.5-10).

[0111] In an embodiment of the present invention, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate, lithium manganese iron phosphate, and ternary positive electrodes (nickel cobalt manganese positive electrode, nickel cobalt aluminum positive electrode).

[0112] In an embodiment of the present invention, the conductive agent includes at least one of oligomeric wall carbon nanotubes, single wall carbon nanotubes, double wall carbon nanotubes, multi-wall carbon nanotubes, conductive carbon black, conductive graphite, and graphene.

[0113] In an embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride, acrylonitrile, vinylidene fluoride, vinyl alcohol, methacryloyl, acrylic acid, lithium acrylate, acrylamide, amide, imide, acrylate, sodium alginate, chitosan, ethylene glycol, monomers, polymers, and copolymers of guar gum.

[0114] In an embodiment of the present invention, the positive electrode current collector is at least one of aluminum foil, electroplated aluminum foil, carbon-coated aluminum foil, porous aluminum foil, carbon-containing porous aluminum foil, foam aluminum foil, and nickel-plated aluminum foil.

[0115] In an embodiment of the present invention, the separator is a polymer separator of at least one of polyethylene, polypropylene, polysulfone, polyacrylonitrile, polyvinyl alcohol, polyarylether sulfone, polyvinylidene fluoride, and polymalonate.

[0116] In an embodiment of the present invention, the battery structure includes but is not limited to coin cells, soft-pack batteries, cylindrical batteries, etc.

[0117] This application places no particular restrictions on the electrolyte in the battery. Those skilled in the art can select according to actual needs as long as the purpose of this application can be achieved.

[0118] The reagents, instruments, materials, etc. used in the present invention can all be obtained through commercial channels.

[0119] The following further elaborates the present invention in conjunction with embodiments:

[0120] Example 1:

[0121] The preparation method of the current collector in this example includes the following steps:

[0122] (1) CuO powder (D 50 is 50 nm), polyethersulfone (PESF), polyvinylpyrrolidone (PVP), indium metal powder (D 50(100 nm) was ball-milled and mixed in a mass ratio of 7:1.95:1:0.05. After adding an appropriate amount of N-methylpyrrolidone (NMP), ball milling was continued at a speed of 800 rpm / min for 5 h to obtain a slurry with stable viscosity, and its viscosity was 6000 mPa·s.

[0123] (2) The uniform and viscous slurry was cast onto a PET carrier film by the single-layer casting method. Then, it was quickly transferred to an ethanol solvent and soaked for 6 h. After the phase inversion process was completed, the green body was taken out and transferred to a drying oven for drying at 80 °C for 14 h. The dried green body was placed in a muffle furnace and sintered at 400 °C for 2.5 h to remove carbon. After completely removing the polymer solute polyethersulfone, a base layer was obtained. Then, the base layer was transferred to a tubular furnace and subjected to reduction sintering at 850 °C for 5 h in an atmosphere of 5% H2 + 95% Ar to obtain a current collector with a vertical channel of lithiumophilic metal@copper composite, and the porosity was 35%.

[0124] (3) Carboxymethyl cellulose (CMC) was added to a certain amount of deionized water and continuously stirred to prepare a solution with a mass fraction of 1.5%. Sodium dodecyl sulfate, an anionic surfactant with a mass ratio of 1% of the solution mass fraction, was added to the CMC solution and stirred evenly to prepare a stable slurry. Subsequently, the slurry was coated on the lithiumophilic metal@copper vertical channel current collector with a thickness of about 8 μm after alcohol cleaning, and the coating thickness was about 2 μm. After being transferred to an oven and dried at 120 °C for 15 h, a current collector with a vertical channel of anionic surfactant-modified lithiumophilic metal@copper composite was obtained. The preparation flow chart is shown in Figure 1 , and the schematic structural diagram of the cross-section of the current collector is shown in Figure 2 .

[0125] Example 2:

[0126] The difference between this example and Example 1 is that the addition amount of the anionic surfactant is 0.5% of the mass of the CMC solution.

[0127] Example 3:

[0128] The difference between this example and Example 1 is that the addition amount of the anionic surfactant is 3% of the mass of the CMC solution.

[0129] Comparative Example 1:

[0130] The current collector of this comparative example is a carbon-coated copper foil.

[0131] Comparative Example 2:

[0132] The difference between this comparative example and Example 1 is that no lithiumophilic metal and no anionic surfactant modification were used. The specific preparation method includes the following steps:

[0133] (1) Mix CuO powder, polyethersulfone (PESF), and PVP in a mass ratio of 7:2:1 by ball milling, add an appropriate amount of NMP, and continue ball milling to obtain a slurry with stable viscosity.

[0134] (2) Cast the homogeneous and viscous liquid slurry onto a PET carrier film using the single-layer casting method, then quickly transfer it to an ethanol solvent and soak for 6 h. After the phase inversion process is completed, take out the green body and transfer it to a drying oven for drying at 80 °C for 14 h. Put the dried green body into a muffle furnace and sinter at 400 °C for 2.5 h to remove carbon, completely remove the polymer solute polyethersulfone to obtain a base layer, and then transfer the base layer to a tubular furnace. Under an atmosphere of 5% H2 + 95% Ar, perform reduction sintering at 850 °C for 5 h to obtain a current collector with vertical channels.

[0135] Comparative Example 3:

[0136] The difference between this comparative example and Example 1 is that it is not modified with an anionic surfactant. The specific preparation method includes the following steps:

[0137] (1) Mix CuO powder, polyethersulfone (PESF), PVP, and indium metal powder (D 50 with a particle size of 100 nm) in a mass ratio of 7:1.95:1:0.05 by ball milling, add an appropriate amount of NMP, and continue ball milling to obtain a slurry with stable viscosity.

[0138] (2) Cast the homogeneous and viscous liquid slurry onto a PET carrier film using the single-layer casting method, then quickly transfer it to an ethanol solvent and soak for 6 h. After the phase inversion process is completed, take out the green body and transfer it to a drying oven for drying at 80 °C for 14 h. Put the dried green body into a muffle furnace and sinter at 400 °C for 2.5 h to remove carbon, completely remove the polymer solute polyethersulfone to obtain a base layer, and then transfer the base layer to a tubular furnace. Under an atmosphere of 5% H2 + 95% Ar, perform reduction sintering at 850 °C for 5 h to obtain a current collector with vertical channels of lithiumophilic metal@copper composite.

[0139] Fabrication and Performance Testing of Lithium Metal Batteries without Anode

[0140] 1. Fabrication of Lithium Metal Batteries without Anode

[0141] Put LiNi 0.6 Co 0.1 Mn 0.3The O2 material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were ground evenly in a mass ratio of 8:1:1. Then, an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil and dried at 80 °C for 1 h in a forced-air drying oven, and then dried at 120 °C for 12 h in a vacuum drying oven. After that, it was cut into 13-mm circular positive electrode sheets using a cutting machine. The current collectors of the above examples and comparative examples were punched into 14-mm round sheets as the negative electrodes. The electrolyte was 1 M LiTFSI dissolved in a mixed solvent of 1,3-dioxolane (DOL) and dimethoxyethane (DME) (1:1), and 2% LiNO3 was added; the separator was a 16-mm-diameter PE separator, and a CR2032 coin cell was assembled in a glove box filled with high-purity argon.

[0142] 2. Performance Test

[0143] (1) Initial discharge capacity and initial Coulombic efficiency:

[0144] Using the constant current charge-discharge mode, charge-discharge tests were carried out at a current density of 0.1C. Under the condition of 25 °C, charge at a constant current of 0.1C to 4.4V, record the charging capacity at this time as the 0.1C initial charging capacity, and then discharge at a constant current of 0.1C to 2.8V, record the discharge capacity at this time as the 0.1C initial discharge capacity; Initial Coulombic efficiency = 0.1C initial discharge capacity / 0.1C initial charging capacity * 100%

[0145] (2) 1C 200-cycle capacity retention rate:

[0146] Under the condition of 25 °C, charge at a constant current of 1C to 4.4V, record the charging capacity at this time as the initial charging capacity; then discharge at a constant current of 1C to 2.8V, record the discharge capacity at this time as the initial discharge capacity; repeat the above charge-discharge process, record the discharge capacity of the 200th cycle, and the capacity retention rate = discharge capacity of the 200th cycle / initial discharge capacity * 100%.

[0147] (3) Lithium deposition on the current collector:

[0148] In the glove box, disassemble the battery after the 0.1C initial charge, take out the negative electrode sheet, soak it in DMC for 15 min, then take it out and send it for scanning electron microscopy to observe the lithium deposition on the current collector.

[0149] Table 1 Performance test results of examples and comparative examples

[0150]

[0151] As can be seen from Table 1, Examples 1 to 3 are non-lithium anode batteries prepared from current collectors of vertically channeled lithiumophilic metal@copper composites modified with anionic surfactants provided by the present invention, and all show good capacity performance and capacity retention rate. After the first charge, the negative current collector of Example 1 was observed under an optical microscope: the lithium deposition was relatively uniform ( Figure 3 ), indicating that the current collector of the vertically channeled lithiumophilic metal@copper composite modified with an anionic surfactant can effectively bind the lithium ions migrating to the negative electrode and inhibit the uneven lithium deposition behavior.

[0152] In Comparative Example 1, a conventional carbon-coated copper foil without a coating was used, showing poor electrochemical performance. After the first charge, the negative current collector was observed under a scanning electron microscope: the lithium deposition was uneven, and there was a problem of lithium dendrite growth ( Figure 4 ).

[0153] In Comparative Example 2, only a copper foil with a vertical current collector structure was used, and the capacity performance at 1C was poor, indicating poor rate performance.

[0154] In Comparative Example 3, the current collector of the vertically channeled lithiumophilic metal@copper composite was not modified with an anionic surfactant, so the capacity performance was poor.

[0155] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A current collector, characterized in that: The current collector comprises: (a) a substrate layer, wherein the substrate layer is provided with a pore structure; the substrate layer contains copper and a lithium-philic metal; (b) a modification layer disposed on at least one surface of the substrate layer; the modification layer comprises an anionic surfactant.

2. The current collector according to claim 1, characterized in that: The lithium-philic metal includes at least one of indium, tin, aluminum, and silver; The particle size D of the lithium-philic metal 50 50~200nm; The mass ratio of the copper to the lithium-philic metal is (5-6): (0.05-0.2).

3. The current collector according to claim 1, characterized in that: The pore structure includes a plurality of vertical channels penetrating the substrate layer; The pore structure has a pore diameter of 20 to 60 nm; The porosity of the substrate layer is 30% to 50%.

4. The current collector according to claim 1, characterized in that: The anionic surfactant includes at least one of sodium dodecyl sulfate, anionic polyacrylamide, and sodium ethoxylated fatty acid methyl ester sulfonate.

5. The current collector according to claim 1, characterized in that: The thickness of the substrate layer is 6 to 13 μm; The thickness of the modified layer is 1 to 3.5 μm.

6. The method for preparing the current collector according to any one of claims 1 to 5, characterized in that: The steps include: S1, mixing copper oxide, polyethersulfone, a dispersant, a lithium-philic metal and a first solvent, and performing ball milling to obtain a first slurry; The first slurry is coated on a carrier film, and then placed in a second solvent for phase inversion reaction, and after a first drying treatment, a green body is obtained; S2, performing a carbon removal treatment on the green body to obtain a base layer; performing a reduction sintering treatment on the base layer to obtain a substrate layer; S3, mixing an anionic surfactant with an aqueous solution of a bonding dispersant to obtain a second slurry; The second slurry is coated on the surface of the substrate layer, and after a second drying treatment, the current collector is obtained.

7. The preparation method according to claim 6, characterized in that: In the step S1, The mass ratio of the copper oxide, the polyethersulfone, the dispersant and the lithium-philic metal is 7:(1.9-1.95):1:(0.05-0.2); The particle size D of the copper oxide 50 10~100nm; The dispersant includes polyvinyl pyrrolidone and / or hydroxypropyl methylcellulose; The first solvent includes N-methylpyrrolidone; The viscosity of the first slurry is 5000-8000 mPa·s; The ball milling speed is 500-800 rpm / min, and the ball milling time is 3-10 hours; The second solvent comprises ethanol; The phase inversion reaction time is 4 to 8 hours; The temperature of the first drying treatment is 80-100° C., and the time of the first drying treatment is 12-24 hours.

8. The preparation method according to claim 6, characterized in that: In the step S2, The temperature of the carbon removal treatment is 380-500°C, and the time of the carbon removal treatment is 2-4 hours; The gas atmosphere of the reduction sintering treatment is a mixed gas atmosphere of hydrogen and inert gas, and the volume ratio of the hydrogen to the inert gas is (4-6): (94-96); The temperature of the reduction sintering treatment is 750-950° C., and the time of the reduction sintering treatment is 4-8 hours.

9. The preparation method according to claim 6, characterized in that: In the step S3, The bonding dispersant includes carboxymethyl cellulose; The concentration of the bonding dispersant aqueous solution is 1wt% to 2wt%; The mass ratio of the anionic surfactant to the aqueous solution of the bonding dispersant is (0.5-3):100; The temperature of the second drying treatment is 100 to 120° C., and the time of the second drying treatment is 12 to 24 hours.

10. A lithium battery, characterized in that: The lithium battery comprises the current collector according to any one of claims 1 to 5, and / or the current collector prepared by the preparation method according to any one of claims 6 to 9.